Stability-Indicating HPLC Determination of Gemcitabine in Pharmaceutical Formulations - Singh, Rahul (Int J Anal Chem, 2015)
A simple, sensitive, inexpensive, and rapid stability indicating high performance liquid chromatographic method has been developed for determination of gemcitabine in injectable dosage forms using theophylline as internal standard. Chromatographic separation was achieved on a Phenomenex Luna C-18 column (250 mm × 4.6 mm; 5μ) with a mobile phase consisting of 90% water and 10% acetonitrile (pH 7.00 ± 0.05). The signals of gemcitabine and theophylline were recorded at 275 nm. Calibration curves were linear in the concentration range of 0.5–50 μg/mL. The correlation coefficient was 0.999 or higher. The limit of detection and limit of quantitation were 0.1498 and 0.4541 μg/mL, respectively. The inter- and intraday precision were less than 2%. Accuracy of the method ranged from 100.2% to 100.4%. Stability studies indicate that the drug was stable to sunlight and UV light. The drug gives 6 different hydrolytic products under alkaline stress and 3 in acidic condition. Aqueous and oxidative stress conditions also degrade the drug. Degradation was higher in the alkaline condition compared to other stress conditions. The robustness of the methods was evaluated using design of experiments. Validation reveals that the proposed method is specific, accurate, precise, reliable, robust, reproducible, and suitable for the quantitative analysis.